Telecommunications demystified : a streamlined course in digital communications (and some analog) for EE students and practicing engineers - Nassar, Carl, 1968- (Demystifying technology series., 2001)
Carl R. Nassar, Ph. D., is professor of telecommunications at Colorado State University and director of the Research in Advanced Wireless Communications (RAWCom) laboratory there. He also consults for telecommunications firms and publishes extensively in the wireless literature. Balances a solid theoretical treatment of subjects with practical applications and examples. Covers both digital and analogue telecommunications systems, including digital modulation techniques. The CD accompanying the book includes MATLAB tutorials that permit readers to model various telecommunications systems and an electronic version of the book.